The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1086/133978
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Abundances and Atmospheric Parameters of Seven F-G Supergiants

Abstract: Spectroscopic abundance determinations for a sample of seven F-G stars have been carried out. The majority of them have large galactic latitudes. One objective in deriving spectroscopic abundances is to differentiate evolved objects seen at high galactic latitudes from the young Population I supergiant stars that happen to have large galactic latitudes but actually belong to the galactic disk. Second, it is important to get good calibrators for photometric metallicity indices. It has been suggested in the past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
1
14
1
Order By: Relevance
“…2. The model parameters slightly differ from the model parameters found by Luck et al (1990) and Giridhar et al (1997). The former authors found (6600 K, 1.5 (cgs), 2.3 km s −1 ), the latter A complete line identification of this spectral interval has been attempted by the use of the VALD database (Kupka et al 1999).…”
Section: Atmospheric Parameters and Equivalent Widthsmentioning
confidence: 61%
“…2. The model parameters slightly differ from the model parameters found by Luck et al (1990) and Giridhar et al (1997). The former authors found (6600 K, 1.5 (cgs), 2.3 km s −1 ), the latter A complete line identification of this spectral interval has been attempted by the use of the VALD database (Kupka et al 1999).…”
Section: Atmospheric Parameters and Equivalent Widthsmentioning
confidence: 61%
“…Somewhat later, Klochkova and Panchuk [16] used photographic spectra taken with the main stellar spectrograph of the Special Astrophysical Observatory (SAO) 6-m telescope to study the spectrum of LN Hya among a sample of supergiants at high Galactic latitudes, and confirmed the main conclusion of Luck et al [15]: LN Hya is a typical post-AGB star with a deficiency of heavy elements. Ten years later, Giridhar et al [17] obtained new estimates of the fundamental parameters and chemical composition of LN Hya based on CCD spectra, reaching similar conclusions. The main focus of the recent study [18] was abundances of elements with low condensation temperatures, which are not subject to selective separation processes (C, N, O, S, Zn).…”
Section: Introductionmentioning
confidence: 70%
“…Both stars are semiregular F supergiants at high Galactic latitudes. The elemental abundances in their atmospheres, studied in [28] for UU Her and in [16,17] for LN Hya, are also similar: their metallicities are [Fe/H] = −1.32 and −1.2, respectively, with considerable excesses of nitrogen and deficiencies of carbon and heavy s-process metals. Significant differences between the two stars include, first, the considerably larger brightness-variation amplitude of UU Her compared to LN Hya (≥ 2 m ), and second, the IR excess of LN Hya, which is absent for UU Her.…”
Section: Emission Components and Line-profile Variationsmentioning
confidence: 87%
“…The calculated data of κ are listed in table 2. From (table 2), it is found that there is general decrease in these values, i.e., decrease in the polarizabilities [29][30][31][32]. …”
Section: Fig (1) Epr Spectra For Obtained Systemmentioning
confidence: 92%
“…The presence of copper as a cluster in the phosphate glass system refers to network modifier of this oxide [27][28]. From the spin Hamiltonian parameters, the dipolar term (P) and the Fermi-contact term (κ) are calculated using the expressions [29][30][31]:…”
Section: Fig (1) Epr Spectra For Obtained Systemmentioning
confidence: 99%